Brazilian guidelines for the management of brain-dead potential organ donors. The task force of the Associação de Medicina Intensiva Brasileira, Associação Brasileira de Transplantes de Órgãos, Brazilian Research in Critical Care Network, and the General Coordination of the National Transplant System. - Westphal, Glauco Adrieno (2021)
Objective: To contribute to updating the recommendations for brain-dead potential organ donor management. Methods: A group of 27 experts, including intensivists, transplant coordinators, transplant surgeons, and epidemiologists, answered questions related to the following topics were divided into mechanical ventilation, hemodynamics, endocrine-metabolic management, infection, body temperature, blood transfusion, and checklists use. The outcomes considered were cardiac arrests, number of organs removed or transplanted as well as function ABSTRACT / survival of transplanted organs. The quality of evidence of the recommendations was assessed using the Grading of Recommendations Assessment, Development, and Evaluation system to classify the recommendations. Results: A total of 19 recommendations were drawn from the expert panel. Of these, 7 were classified as strong, 11 as weak and 1 was considered a good clinical practice. Conclusion: Despite the agreement among panel members on most recommendations, the grade of recommendation was mostly weak